Development of an automatic lighter packaging system for small and medium scale industries - Aris I.B.; Teh C.C.; Koh S.P. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper deals with the design and development of a low cost Cartesian robotic arm for use in an automatic lighter packaging system. The proposed robotic arm consists of hardware and software parts. The hardware part involves with the design and development of a controller, a gripper, a product placement module, a positioning module, a sensing module and a system power supply. The design of the software deals with writing a main program for controlling the operation of the proposed robotic arm, which includes routines such as home, reset, process, jog and error. A smart step controller is used as the main controller of the proposed robotic arm. A working prototype of the robotic arm is developed and tested. The test results show that the proposed robotic arm can perform its dedicated functions accurately in the lighter packaging process. 2003 IEEE.